Bedtime Procrastination Partially Mediates the Impact of Personality Characteristics on Daytime Fatigue Resulting From Sleep Deficiency - Herzog-Krzywoszanska, Radoslawa; Jewula, Beata; Krzywoszanski, Lukasz (Frontiers in Neuroscience, 2021)
Getting good and sufficiently long sleep at night is important for health, effective functioning, and well-being. However, insufficient or delayed sleep are important and growing social problems that can lead to fatigue, poor performance, deterioration of well-being, circadian rhythm disturbances, and health problems. One of the significant determinants of sleep deprivation is bedtime procrastination, which is understood as the individual tendency to postpone going to bed in the absence of any external circumstances that force one to do so. Nowadays, this phenomenon is widespread in various social groups, especially among students. Despite the high prevalence of bedtime procrastination, its relationship with personality characteristics has not yet been thoroughly studied. The presented research aimed to identify the possible impact of the basic dispositional personality traits and trait-like personality characteristics on bedtime procrastination and daytime fatigue resulting from a deficiency of sleep at night. The responses from 399 university students who voluntarily took part in an internet survey were analyzed. The severity of bedtime procrastination was assessed using the Bedtime Procrastination Scale. Five basic dispositional personality traits (extraversion, neuroticism, conscientiousness, agreeableness, and openness/intellect) and their components (aspects) were measured using the International Personality Item Pool – Big Five Aspects Scale. Self-esteem and general self-efficacy were assessed using the Rosenberg Self-Esteem Scale and the General Self-Efficacy Scale. Perceived locus of control was measured using the Delta Questionnaire. The direct and indirect relationships between personality variables and daytime fatigue were investigated using linear regression models with bedtime procrastination as a mediator variable. Industriousness and orderliness, both of which are aspects of conscientiousness, were found to be indirectly associated with daytime fatigue as a consequence of their impact on bedtime procrastination. Volatility and withdrawal, both of which are aspects of neuroticism, were found to be directly related to daytime fatigue without the intermediary impact of bedtime procrastination. Self-esteem was shown to be associated with experiencing daytime fatigue, both directly and indirectly through bedtime procrastination. General self-efficacy and external locus of control were associated with daytime fatigue only directly, without the intermediary role of bedtime procrastination. The results of our research indicate that personality factors may not only play an important role in shaping sleep-related health behaviors, but they also affect well-being during the day.